Associations of computer gaming with incident dementia, cognitive functions, and brain structure: a prospective cohort study and Mendelian randomization analysis - Jia, Yiming; Shi, Mengyao; Yang, Pinni; Wang, Ruirui; Sun, Lulu; Wang, Yinan; Xu, Qingyun; Zhang, Jing; Zhang, Qilu; Guo, Daoxia; Zheng, Xiaowei; Liu, Yi; et al. (Alzheimer's research & therapy, 2024)
Computer gaming has recently been suggested to be associated with benefits for cognition, but its impact on incident dementia remains uncertain. We aimed to investigate the observational associations of playing computer games with incident dementia, cognitive functions, and brain structural measures, and further explore the genetic associations between computer gaming and dementia. We included 471,346 White British participants without dementia at baseline based on the UK Biobank, and followed them until November 2022. We estimated the risk of dementia using Cox proportional hazard models, and assessed the changes of cognitive functions and brain structural measures using logistic regression models and linear regression models. Mendelian randomization (MR) analyses were performed to examine the association between genetically determined computer gaming and dementia. High frequency of playing computer games was associated with decreased risk of incident dementia (HR, 0.81 [95% CI: 0.69, 0.94]). Individuals with high frequency of playing computer games had better performance in prospective memory (OR, 1.46 [1.26, 1.70]), reaction time (beta, -0.195 [-0.243, -0.147]), fluid intelligence (0.334 [0.286, 0.382]), numeric memory (0.107 [0.047, 0.166]), incorrect pairs matching (-0.253 [-0.302, -0.203]), and high volume of gray matter in hippocampus (0.078 [0.023, 0.134]). Genetically determined high frequency of playing computer games was associated with a low risk of dementia (OR, 0.37 [0.15, 0.91]). Computer gaming was associated with a decreased risk of dementia, favorable cognitive function, and better brain structure, suggesting that computer gaming could modulate cognitive function and may be a promising target for dementia prevention.